Olimpiada Peruana de Química 2016-2017: el camino a lo más alto - Ortega-San-Martín, Luis; Gonzales Gil, Patricia; Chong Cáceres, Miguel; Cabello Liu, Isabel (Pontificia Universidad Católica del Perú, 2017)
The years 2016 and 2017 have allowed consolidating the position and importance of the Peruvian Chemistry Olympiad as an activity that encourages the study of chemistry and the desire to improve in today's students. Although 2016 ended with good results at the international level, the successes achieved in 2017 have overshadowed them: one gold and one bronze medals in the IChO 2017 and one gold and three silver medals in the OIAQ. Nationally, the Peruvian Chemistry Olympiad (OPQ) has maintained the high level of enrollment and in 2017 we have again exceeded two thousand participants.

Los años 2016 y 2017 han permitido consolidar la posición y la importancia de la olimpiada peruana de química a nivel nacional como una actividad que fomenta el estudio de la química y el esfuerzo de superación. Si bien 2016 se saldó con buenos resultados a nivel internacional, los éxitos conseguidos en 2017 han opacado todo lo ya conocido: una medalla de oro y una de bronce en la IChO 2017 y una de oro y tres de plata en la OIAQ lo dicen todo. Han sido los años de la consagración de un sueño a nivel internacional: la obtención de una medalla de oro. A nivel nacional, la Olimpiada Peruana de Química (OPQ) ha mantenido el alto nivel de inscritos y 2017 ha vuelto a superar los dos mil participantes.
Peruvian Chemistry Olympiad 2016-2017: the path to success
Keywords: OIAQ; IChO; OPQ; https://purl.org/pe-repo/ocde/ford#1.04.00